Increasing Public Legal Awareness of Rights and Obligations as Consumers in Online Transactions - salim; Chairus Suriyati (Outline Publisher, 2023)
This activity aims to analyze the level of consumer legal awareness of their rights and obligations in digital transactions and identify obstacles in law enforcement in this area. The method used is a socio-legal approach with a combination of qualitative and participatory, including interviews, observations, and socialization of legal education to the community. The results of the study showed that before the socialization, public understanding of consumer protection regulations was still low. However, after education, the level of understanding increased by 70%, although challenges in implementing legal protection remain. The main obstacles include lack of access to information, low trust in complaint mechanisms, and weak supervision of e-commerce platforms. This study recommends increasing legal education, strengthening regulations, and collaboration between the government, business actors, and the community in creating safer online transactions. With better legal awareness, it is hoped that consumers can protect their rights more effectively, so that the digital economy ecosystem can develop fairly and sustainably.